intsu11smue

intsu11smue - Introductory Number Theory.Topics for the...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Introductory Number Theory.Topics for the make up exam 1. Prove: There exists an infinity of prime numbers. 2. True or false: n 2 81 n + 1681 is prime for all n N ? 3. Prove that the product of any three consecutive numbers is divisible by 6. 4. Let b N , b 1. Prove that every a N can be expressed in the form a = d n b n + + d 1 b + d = n k =0 d k b k for a unique n Z , n 0,unique d , . . . , d n { , 1 , . . . , b 1 } , d n = 0. Hint: This is, of course, the representation of a in base b . Uniqueness means that if n k =0 d k b k = m j =0 e j b j , d n = 0 = e n , d k , e j { , 1 , . . . , b 1 } then n = m and d k = e k for 0 k n . One way of proving this is to say that without loss of generality we may assume that m n , and if m < n , set e m +1 = = e n = 0, so we now deal with the same number of digits. It now suces to prove that d k = e k for k = 0 , . . . , n . This automatically implies n = m , because then e n = d n = 0, so we must have had n = m . For a contradiction assume that not all digits are equal; there exists then a last k , 0 k n such that d k = e k . For example, if n > m , this last one will already be d n ; i.e., k = n . If k < k n , then d k = e k . (If k = n , then the set k < k n is empty.) Without loss of generality we may assume d k > e k ; the proof if e k > d k is identical. We now have d k b k + + d 1 b + d = e k b k + + e 1 b + e (since the terms preceding the k term are all equal). If k = 0 we have an immediate contradiction: d = e (since with k = 0 wed have d > e ), so henceforth we assume k 1. Rearranging the equation, ( d k e k ) b k = ( e k- 1 d k- 1 ) b k- 1 + + ( e 1 d 1 ) b + ( e d ) . On the RHS, | e k d k | b 1, thus the RHS of this equation satisfies | ( e k- 1 d k- 1 ) b k- 1 + +( e 1 d 1 ) b +( e d ) | ( b 1) ( b k- 1 + + b + 1 ) = ( b 1) b k 1 b 1 = b k 1 < b k ....
View Full Document

This note was uploaded on 07/13/2011 for the course MAS 3202 taught by Professor Staff during the Summer '11 term at FAU.

Page1 / 4

intsu11smue - Introductory Number Theory.Topics for the...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online